2018
DOI: 10.3390/v10040146
|View full text |Cite
|
Sign up to set email alerts
|

Enteric Virome Sensing—Its Role in Intestinal Homeostasis and Immunity

Abstract: Pattern recognition receptors (PRRs) sensing commensal microorganisms in the intestine induce tightly controlled tonic signaling in the intestinal mucosa, which is required to maintain intestinal barrier integrity and immune homeostasis. At the same time, PRR signaling pathways rapidly trigger the innate immune defense against invasive pathogens in the intestine. Intestinal epithelial cells and mononuclear phagocytes in the intestine and the gut-associated lymphoid tissues are critically involved in sensing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 280 publications
(359 reference statements)
2
53
0
Order By: Relevance
“…Intestinal microbes are intimately linked with the immune system of the host (Zhu et al, 2017;Metzger et al, 2018). There is a mutually beneficial relationship between the microorganisms and the host.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal microbes are intimately linked with the immune system of the host (Zhu et al, 2017;Metzger et al, 2018). There is a mutually beneficial relationship between the microorganisms and the host.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, enterovirus surface antigen can be recognized directly by relevant intestinal mucosal immune cells through the cytosolic sensors, retinoic acid inducible gene I, melanoma differentiation-associated protein 5, endosomal TLRs, as well as PRRs, which function to induce further production of IFN (97). Certain viruses, such as phages, are also closely associated with bacterial diversity, which indirectly plays a role in the intestinal immune system and contributes to development of disease.…”
Section: Disorders Of Intestinal Flora Affect the Relationship Betweementioning
confidence: 99%
“…Recent studies have shed light on how resident enteric viruses may affect host physiology beyond causing disease [90]. Despite the partial picture of the taxonomic composition of the mammalian virome, recent investigations showed that the preponderance of viruses residing in the intestine are bacteriophages, which infect bacteria and can be released from them in response to stress signals [91].…”
Section: The Interplay Between the Microbiome And Virome: A New Visiomentioning
confidence: 99%
“…A different study performed on mice showed activation of myeloid differentiation primary response 88 (MyD88)-dependent pathway, with consequent involvement of TLRs [95]. Despite controversial results, it is clear that enteric phages have a key role in the modulation of the bacterial microbiome on the intestinal mucosal surface [90].…”
Section: The Interplay Between the Microbiome And Virome: A New Visiomentioning
confidence: 99%